HUBUNGAN ANTARA OPTIMISME DENGAN PROBLEM FOCUSED COPING PADA MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI - Indawati S.Psi.; Nanik Kholifah (Ilmu Psikologi Universitas Yudharta Pasuruan)
The purpose of this study is to determine the relationship between optimism and problem focused coping on students who are working on thesis. Methods of data collection in this study using the optimism scale to measure the level of optimism in the student and the scale of problem focused coping to measure how a student in dealing with and overcoming stress when doing thesis by looking for various information. To find out the relationship between optimism with problem focused coping on students who do thesis, data obtained then processed by using product moment correlation technique from Pearson. From the calculation of the correlation obtained rxy = 0.1693 with t-table 5% = 0.254 and t-table 1% = 0.330, then obtained rxy <t-table 5%, so expressed unsignificant. Which means there is no relationship between optimism (X) with problem focused coping (Y) on students who are working on thesis. Thus the hypothesis which states